2019
DOI: 10.1111/1365-2435.13496
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate phenology modulates the effect of the leaf economics spectrum on litter decomposition rate across 41 subtropical woody plant species

Abstract: Litter quality and decomposers are critical to carbon and nutrient cycling through litter decomposition. However, how relationships between litter quality and invertebrate detritivores change litter mass loss through time is poorly known. Species’ initial leaf litter quality, as a legacy of their position on the ‘leaf economics spectrum’ (LES), may determine the invertebrate contribution to litter mass loss. This contribution may change through time, as both population peaks of invertebrate detritivores and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…While, without the involvement of invertebrate decomposers wood decomposition rates were predicted by initial values along the WES, when termites participated in the decomposition process they actively altered the species' ranking in terms of the WES through time and moved in abundance and activity from initially high WES species to initially medium WES species. These findings have an interesting parallel with a recent study that found a modulating effect of invertebrate consumption on leaf mass loss rankings along an axis of initial litter quality, i.e., the leaf economics spectrum, over time (Guo et al 2019). However, in that study the modulation was due to a single outbreak by detritivorous moth larvae, while in this study the decomposing invertebrates (i.e., termites) were present in considerable abundance through time in the studied forests, but changed their relative abundance and contribution to decomposition among tree species as decomposition progressed.…”
Section: Discussionsupporting
confidence: 82%
“…While, without the involvement of invertebrate decomposers wood decomposition rates were predicted by initial values along the WES, when termites participated in the decomposition process they actively altered the species' ranking in terms of the WES through time and moved in abundance and activity from initially high WES species to initially medium WES species. These findings have an interesting parallel with a recent study that found a modulating effect of invertebrate consumption on leaf mass loss rankings along an axis of initial litter quality, i.e., the leaf economics spectrum, over time (Guo et al 2019). However, in that study the modulation was due to a single outbreak by detritivorous moth larvae, while in this study the decomposing invertebrates (i.e., termites) were present in considerable abundance through time in the studied forests, but changed their relative abundance and contribution to decomposition among tree species as decomposition progressed.…”
Section: Discussionsupporting
confidence: 82%
“…2018, Guo et al. 2019), while to our knowledge no such clear pattern has been found for roots as yet (Fujii et al. 2018).…”
Section: Introductionmentioning
confidence: 82%
“…Additionally, red maple can decompose quickly [ 33 , 34 ], thus enabling the assessment of early decay dynamics. We collected healthy fresh rather than senesced leaves directly from living trees to standardize the initial conditions of the substrate, an experimental approach that can be used to compare among treatments [ 35 ]. The same day of collection, the leaves were dried in an industrial oven at 70º C for 24h to measure the initial dry-weight ( M 0 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study we only capture the early stages of leaf litter loss, though acknowledge that early decomposition dynamics are different from those in the late decomposition period [ 35 ]. Nonetheless, in studies that evaluate decomposition for longer periods, the importance of invertebrate exclusion becomes evident after 30 days (e.g.…”
Section: Methodsmentioning
confidence: 99%